Last active
March 2, 2025 21:06
-
-
Save jcreedcmu/ecb75dc1bd907d20d6cd1b95527a3936 to your computer and use it in GitHub Desktop.
Prime Ideals and Functions
This file contains bidirectional Unicode text that may be interpreted or compiled differently than what appears below. To review, open the file in an editor that reveals hidden Unicode characters.
Learn more about bidirectional Unicode characters
Claim: there's a bijection between prime ideals of a commutative ring R | |
(I is a prime ideal of R iff: | |
(1) (I, +) is a subgroup of (R, +) | |
(2) if r ∈ R and x ∈ I, then rx ∈ I | |
(3) if ab ∈ I, then a ∈ I or b ∈ I | |
(4) 1 ∉ I) | |
and maps f : R → 2 s.t. | |
(a) f(0) = 0 | |
(b) f(1) = 1 and f(-1) = 1 | |
(c) f(a * b) = min(f(a), f(b)) | |
(d) f(a + b) ≤ max(f(a), f(b)) | |
Proof sketch: | |
### Direction from ideal to function. | |
If we have a prime ideal I, convert it to a function f by | |
setting | |
f(x) = x ∈ I ? 0 : 1 | |
I ⊆ R means f(0) = 0 and f(a) = 0 and f(b) = 0 imply f(a + b) = 0 | |
1 ∉ I means f(1) = 1 | |
Also if I is a subgroup, we have to have f(-1) = 1, because if f(-1) = 0, | |
then f(1) = 0, a contradiction. | |
So we have (a) and (b) | |
(3) means that if f(a) = 1 and f(b) = 1, then f(ab) = 1. | |
(2) means that if f(a) = 0, then f(ab) = 0. | |
So combining (2) and (3), we have (c). | |
All that remains is (d). | |
Consider all possibilities for f(a) and f(b). | |
If f(a) = f(b) = 0, we must show f(a + b) = 0. But this follows from (1). | |
Otherwise max(f(a), f(b)) = 1, and f(a + b) ≤ 1 is trivially true. | |
### Direction from function to ideal | |
If we have a function f : R → 2, then I is defined by | |
I = {x ∈ R | f(x) = 0} | |
We have f(0) = 0. We have that if f(a) = 0 and f(b) = 0, then | |
f(a + b) = 0, by (d). Suppose f(a) = 0. Is it the case that f(-a) = 0? | |
Well, f(-a) = f(-1 * a) = min(f(-1), f(a)) = min(1, f(a)) = f(a) = 0, | |
so yes. | |
So we have (1). | |
For (2), we must show If r ∈ R and f(x) = 0, then f(xr) = 0. But this follows from (c). | |
For (3), we must show that if f(ab) = 0, then f(a) = 0 or f(b) = 0. But this is | |
the contrapositive of f(a) = 1 and f(b) = 1 implies f(ab) = 1, an instance of (c). | |
Finally, (4) follows from (b). |
Agreed, I hope it points the way to something cleaner :)
Sign up for free
to join this conversation on GitHub.
Already have an account?
Sign in to comment
Ugly but true :-)